2016
DOI: 10.3390/rel7040041
|View full text |Cite
|
Sign up to set email alerts
|

Protocol of Taste and See: A Feasibility Study of a Church-Based, Healthy, Intuitive Eating Programme

Abstract: Obesity treatment remains a high global priority. Evidence suggests holistic approaches, which include a religious element, are promising. Most research is from the USA, but recent evidence suggests a need within the UK population. The aim of this study is to explore the feasibility of running and evaluating a Christian-based, healthy, intuitive-eating programme, in a UK church. This is the protocol of a mixed-methods single-group feasibility study of a ten-week programme. The programme focuses on breaking the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…"Taste & See" is an intervention that views obesity as a chronic, relapsing, remitting condition, and aims to reduce the harms associated with it; rather seeking weight loss at all costs. The design of the "Taste & See" programme and the protocol for testing the feasibility of this was previously reported in Religions (Lycett et al 2016). The results of the feasibility study, also previously reported in Religions, showed this programme could be run successfully by church volunteers and improvements in participants' mental well-being, emotional eating and quality-of-life were observed during and for six months after the programme (Patel et al 2017a).…”
Section: Introductionmentioning
confidence: 58%
See 1 more Smart Citation
“…"Taste & See" is an intervention that views obesity as a chronic, relapsing, remitting condition, and aims to reduce the harms associated with it; rather seeking weight loss at all costs. The design of the "Taste & See" programme and the protocol for testing the feasibility of this was previously reported in Religions (Lycett et al 2016). The results of the feasibility study, also previously reported in Religions, showed this programme could be run successfully by church volunteers and improvements in participants' mental well-being, emotional eating and quality-of-life were observed during and for six months after the programme (Patel et al 2017a).…”
Section: Introductionmentioning
confidence: 58%
“…The intervention consists of 10 weekly sessions which takes the participants on a journey from identifying problematic eating behaviours to begin making changes. The programme incorporates 25 behavior change technique (Michie et al 2013) and is described more fully in the feasibility study protocol (Lycett et al 2016). The programme resources have now been developed into a 'off the shelf' prototype package which is sent to churches to be delivered locally by the programme facilitators.…”
Section: Intervention Programmementioning
confidence: 99%
“…This community-based programme may be more responsive than more traditional medical approaches, and several reliable measures are proposed that will likely produce interesting results. The authors [33] hypothesize positive results with their intervention. The subject of prayer is also addressed by Simão et al [34].…”
Section: Interventions and Outcomesmentioning
confidence: 99%
“…Lycett et al [33] describe a planned methodology for a ten-week "church based, health, intuitive eating programme" aimed at assisting weight loss. They provide convincing evidence of the need for this type of study and demonstrate how local churches may become active in health promotion.…”
Section: Interventions and Outcomesmentioning
confidence: 99%
“…None of the lay facilitators had a healthcare background and their experience in dealing with people who had significant weight and food issues was limited. The lay facilitators were taught about programme content, the importance of listening and supporting participants' own behaviour change solutions rather than providing advice, and when to signpost individuals to healthcare professionals (further details on training provided is in the protocol paper) [15]. The study dietitian/principal investigator (DL), supported by RP demonstrated initial sessions and facilitators took on more responsibility for delivery as the programme progressed.…”
Section: Facilitatorsmentioning
confidence: 99%